Implementation of the Snowball Throwing Learning Model Assisted by Flashcard Media in the Science Subject for Grade V - Herfiana, Dela; Mulyono, Dodik; Valen, Andri (Global Education Journal, 2025)
The existence of human education can develop the potentials that exist in him so that he becomes a human being who has a good personality, intelligence, and morals. This study aims to determine the effect of the application of the Snowball Throwing learning model assisted by flashcard media on the learning outcomes of fifth-grade students in SD Negeri Durian Remuk. This study uses a quantitative approach with a quasi-experimental method in the form of a one-group pretest-posttest design. The subjects in this study were fifth-grade students of SD Negeri Durian Remuk in the 2024/2025 academic year. The results showed that the average pretest score (initial test) was 46.96 with a standard deviation of 11.39, while the average posttest score (final test) increased to 84.35 with a standard deviation of 10.28. The normality test shows that the pretest and posttest data are normally distributed because the calculated χ² value is smaller than the χ² table, which is 0.7824 < 9.488 for the pretest and 0.7763 < 9.488 for the posttest. Furthermore, the results of the analysis using the Z test at a significance level of α = 0.05 show that Zcount = 9.04 > Ztable = 1.64, so that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the application of the Snowball Throwing learning model assisted by flashcard media can significantly improve the science learning outcomes of fifth-grade students of Durian Remuk State Elementary School and achieve learning completeness with a value category of ≥ 65.